Plasma Concentrations of Boswellic Acids in Fasting Healthy Humans Supplemented with a Water-Soluble Boswellia Extract (78% AKBA) vs. Reference Boswellia Extract (30% AKBA) (P06-005-19). (13th June 2019) - Davis, Barbara; Sengupta, Krishanu; Alluri, Venkata Krishnaraju; Golakoti, Trimurtulu
Abstract: Objectives: A randomized, open label, balanced, two-way crossover study compared the oral bioavailability and pharmacokinetic profiles of two Boswellia products standardized to 3-O-acetyl-11-Keto-β-boswellic acid (AKBA). Methods: Twenty-two fasted male participants completed the study. They received a single oral-dose of water-soluble Boswellia extract 78% (LI51202F1) or the standard Boswellia extract 30% (5-Loxin) at 30 mg AKBA equivalent with 240 mL water on 2 separate occasions 12 days apart. Plasma AKBA and KBA were analyzed using a LC-MS/MS in pre- (0 hr) and post-dose (00.50, 01.00, 01.50, 02.00, 02.50, 03.00, 04.00, 08.00, 12.00 and 24.00 hrs) blood samples. Pharmacokinetic analysis was performed using WinNonlin® version 7.0 (Pharsight corporation, USA). Results: Comparative analysis of the pharmacokinetic parameters showed LI51202F1 had higher (111.11%) Cmax for AKBA vs. 5-Loxin. The bioavailability indicated by Geometric means of AUC0-t and AUC0-∞ were 25.49% and 16.13% higher in LI51202F1 than 5-Loxin. Conclusions: The present study demonstrates that oral ingestion of water soluble and standard Boswellia extracts resulted in similar bioavailability. Interestingly, the water-soluble version exhibited higher Cmax and AUC values, which could be attributed to the improved solubility of LI51202F1. Funding Sources: Laila Nutraceuticals.